Pengembangan Bahan Ajar Biologi Berbasis Multimedia untuk Siswa Kelas VIII SMP Islam Yakin Tutur Kabupaten Pasuruan - Agustiya Handayani; Punaji Setyosari; Sulthoni (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
The purpose of this development is to produce multimedia-based biology teaching materials and teacher instructions for use of biology subjects for eighth grade students of SMP ISLAM YAKIN Tutur, Pasuruan Regency. The development model used in the development of Media-Based Biology Teaching Materials is the Dick and Carey model. Based on the results of the validation and testing of Biology Teaching Materials Based on Media, it can be reported as follows: (1) validation of material experts shows a result of 88%, (2) validation of media experts to show results of 87%, (3) individual trials of students towards showing results of 93%, (4) small group trials to students to showing results of 94%, (5) field trials to students of showing results of 92%. Overall, it can be concluded that the product that has been developed is feasible and valid for use as a learning resource. Suggestions in this development consist of product utilization and further development. For the use of the product, it is suggested that the teacher be able to use learning strategies that can increase the activities and roles of students during the learning process. For further development, it is hoped that there will be further experimental research to measure the effectiveness of Media-Based Biology Teaching Materials.